Collective Entrepreneurship in the Contemporary European Services Industries A Long Term Approach - Fernández Pérez, Paloma (Frontiers of Management History Series, 2023)
Collective Entrepreneurship in the Contemporary European Services Industries provides a historical account and a managerial approach on how companies in the service industry have grown, innovated, and internationalised along the last centuries in Western Europe